Competences for Pharmacy Education and Practice in Europe - Jeffrey Atkinson (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. [One of the main aspirations of the European Union (EU) is the development of a pan-European health system with unhindered access to quality care, in all member states. The PHAR-QA "Quality Assurance in European Pharmacy Education and Training" project explored the realities surrounding this idea in the area of pharmacy. This book assembles a series of papers, already published in the journal "Pharmacy", that describe the project: its origins, design, implementation, results, interpretation, and perspectives.]